Dermoscopy of follicular dowling-degos disease - Garima Dabas; Rahul Mahajan; T P Afra; Dipankar De; Sanjeev Handa; Divya Aggarwal; Bishan Das Radotra (Wolters Kluwer Medknow Publications, 2020)
Dowling-Degos disease (DDD) is a late-onset genodermatosis characterized by hyperpigmented macules on the flexures along with scattered comedo-like lesions and pitted acneiform scars. Follicular Dowling-Degos is a rare type of DDD, with only two reports so far. It presents with follicular papules and comedo-like lesions predominantly on the face and trunk. Dermoscopy of follicular DDD shows irregular star-shaped/Chinese letter pattern pigmentation along with comedo-like lesions. Herein, we describe diagnostic clues including dermoscopy in three patients of follicular DDD which can help in differentiating it from other disorders presenting with comedo-like lesions .